Penerapan Anggaran Penjualan Sebagai alat Perencanaan dan Pengendalian Persediaan Barang Jadi untuk Mengoptimalkan Laba : Studi Kasus di CV Wecono Asri - Netty Nasifa Aurasari; Eni Srihastuti; Agus Athori (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This research discusses the application of the sales budget as a tool for planning and controlling finished goods inventory. The aim of this research was carried out based on the application of a sales budget to find out how to implement a sales budget which can be used as a planning and control tool for finished goods inventory to optimize profits at CV Wecono Asri. The type of research used in this research is descriptive quantitative, namely providing a picture of the actual situation of the object under study based on facts, by collecting data processing such as collecting related data, namely raw material costs, labor costs and factory overhead costs. The data examined in this research is from 2021 to 2022 as a basis for calculating sales forecasts in 2023 which will then be prepared for implementing the sales budget. From the results of the research that has been carried out, it shows that the implementation of the sales budget at CV Wecono Asri is more controlled compared to before the sales budget was prepared because the resulting acquisition costs also increase due to the difference between the profit and loss budget report and the profit and loss realization report, which produces results The final difference in profit and loss was IDR 16,660. So with these results it is recommended that CV Wecono Asri prepare a sales budget, production budget, raw materials budget, labor budget and factory overhead budget, the company will get a greater profit than the previous year.